Influence of visual feedback sampling on obstacle crossing behavior in people with Parkinson's disease - Vitório, Rodrigo [UNESP]; Lirani-Silva, Ellen [UNESP]; Barbieri, Fabio Augusto [UNESP]; Raile, Vivian [UNESP]; Stella, Florindo [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (Elsevier, 2013)
The purpose of the current study was to investigate the role of visual information on gait control in people with Parkinson's disease as they crossed over obstacles. Twelve healthy individuals, and 12 patients with mild to moderate Parkinson's disease, walked at their preferred speeds along a walkway and stepped over obstacles of varying heights (ankle height or half-knee height), under three visual sampling conditions: dynamic (normal lighting), static (static visual samples, similar to stroboscopic lighting), and voluntary visual sampling. Subjects wore liquid crystal glasses for visual manipulation. In the static visual sampling condition only, the patients with Parkinson's disease made contact with the obstacle more often than did the control subjects. In the successful trials, the patients increased their crossing step width in the static visual sampling condition as compared to the dynamic and voluntary visual sampling conditions; the control group maintained the same step width for all visual sampling conditions. The patients showed lower horizontal mean velocity values during obstacle crossing than did the controls. The patients with Parkinson's disease were more dependent on optic flow information for successful task and postural stability than were the control subjects. Bradykinesia influenced obstacle crossing in the patients with Parkinson's disease. © 2013 Elsevier B.V.
Keywords: Gait; Motor control; Optic flow; Parkinson's disease; aged; ankle; body posture; bradykinesia; clinical article; controlled study; gait; human; locomotion; optic flow; Parkinson disease; priority journal; stroboscopy; task performance; visual feedback; visual information; walking speed